The association between insulin resistance-related markers and ASCVD with hyperuricemia: results from the 2005 to 2018 National Health and Nutrition Examination Survey - Yujie Shi; Zuo Zhang; Jiajun Yang; Song Cui (Frontiers in Cardiovascular Medicine)
BackgroundThe association between insulin resistance and the comorbidity of ASCVD with hyperuricemia remains to be further explored. This study utilizes several insulin resistance indicators, including HOMA-IR, METS-IR, TyG, TyG-WHtR, TyG-WC, and TyG-BMI, to assess insulin resistance levels and investigate their association with the comorbidity of ASCVD and hyperuricemia in the study population.MethodsThis cross-sectional study included 16,092 participants from the National Health and Nutrition Examination Survey conducted between 2005 and 2018. Participants younger than 20 years old and those with missing data for exposure-related indicators were excluded. Six insulin resistance-related traditional and novel indicators—HOMA-IR, METS-IR, TyG, TyG-WC, TyG-WHtR, and TyG-BMI—were used as exposure factors, while the outcome was ASCVD with hyperuricemia. This study's analyses incorporated sample weights, clustering, and stratification to account for the complex multi-stage stratified probability sampling design employed in NHANES.ResultsA total of 523 patients were diagnosed with ASCVD with hyperuricemia. The results were adjusted for different covariates. METS-IR showed a consistent positive correlation with the outcome in all models, with model 3 indicating that for each unit increase, the OR was 1.04 (95% CI: 1.03–1.05, p < 0.0001). The study results showed that TyG-WC, TyG-WHtR, and TyG-BMI remained significantly associated across all models, with TyG-WHtR exhibiting the strongest association (OR = 1.64, 95% CI: 1.37–1.97, p < 0.0001). Furthermore, RCS results showed significant nonlinear relationships for HOMA-IR, METS-IR, TyG-WC, TyG-WHtR, and TyG-BMI with ASCVD with hyperuricemia (p-overall < 0.05, p-nonlinear < 0.05). The ROC analysis revealed high AUC values for TyG-BMI and METS-IR, with AUCs of 0.942 and 0.941. TyG-WC and TyG-WHtR also showed relatively high AUC values of 0.902 and 0.899, respectively. In the calibration curve analysis, METS-IR demonstrated the highest calibration performance.ConclusionsThis NHANES-based study highlighted significant associations between insulin resistance indices, particularly METS-IR, TyG-WC, and TyG-WHtR, and ASCVD with hyperuricemia. Furthermore, it demonstrated the strong predictive capabilities of these indices for identifying individuals at risk for this comorbidity. These findings offer valuable insights into early detection and preventive strategies for ASCVD combined with hyperuricemia, emphasizing the practicality of these indices in clinical and public health settings.